2011
DOI: 10.1292/jvms.10-0252
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Edwardsiella tarda Isolated from Farm-Cultured Eels, Anguilla japonica, in the Republic of Korea

Abstract: ABSTRACT. We surveyed the occurrence of edwardsiellosis on eel farms and investigated the characteristics of Edwardsiella tarda isolated from farm-cultured eels in the Republic of Korea. The occurrence rate of edwardsiellosis was 72% in the investigated samples. Among the edwardsiellosis cases, 46% were found to be mixed infections, with parasites and other kinds of bacteria. Some of the biochemical characteristics of the E. tarda isolates were different from those of the previously reported E. tarda isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Additionally, E. tarda can be classified into two biotypes (wild and biogroup 1) based on the production of H 2 S as described in previous studies (Joh et al . ). However, the biogrouping may be a limited discriminating tool among phenotypic characteristics owing to the diversity of biochemical characteristics.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, E. tarda can be classified into two biotypes (wild and biogroup 1) based on the production of H 2 S as described in previous studies (Joh et al . ). However, the biogrouping may be a limited discriminating tool among phenotypic characteristics owing to the diversity of biochemical characteristics.…”
Section: Resultsmentioning
confidence: 97%
“…Some previous study about the disease that usually attacks the eel is bacteria. Joh et al (2010) have reported the characteristics of Yersinia ruckeri bacteria isolated from a rearing pool of Anguilla japonica in Korea. In addition to Yersinia ruckeri, other pathogenic bacteria that attacked the A.japonica in Korea was Edwardsiella tarda, Aeromonas hydrophila, Aeromonas salmonicida, Aeromonas veronii, Streptococcus iniae, Citrobacter friend, and Vibrio alginolyticus (Joh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…E. tarda has been recognised as one of the major bacterial pathogens to freshwater-and marine-farmed fish species worldwide (Xu and Zhang 2014). In Korea, China and Japan olive flounder and eels are main species that are affected by E. tarda in (Kanai et al 1988;Han et al 2006;Joh et al 2010;Xu and Zhang 2014). E. tarda has also been reported as a rare human pathogen.…”
Section: Introductionmentioning
confidence: 99%